Factors Influencing Women Entrepreneurship and Empowerment in Nepalese Enterprises - Thapa, Sajju (Nepalese Journal of Management, 2024)
This study examines the factors influencing women entrepreneurship and empowerment in Nepalese enterprises. Women empowerment is the dependent variable. The selected independent variables are access to finance, level of education, family and social support, technological skills, and security issue. The primary source of data is used to assess the opinions of respondent’s access to finance, level of education, family and social support, technological skills, and security issue. The study is based on primary data of 132 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of factors influencing women entrepreneurship and empowerment in Nepalese enterprises.The study showed a positive impact of access to finance on women empowerment. It indicates that financial support leads to higher level of women empowerment. Similarly, the study showed a positive impact of level of education on women empowerment. It indicates that higher the level of education, higher would be the women empowerment. Likewise, the study also revealed a positive impact of family and social support on women empowerment. It indicates that support from family and society helps to boost the morale of women empowerment. Further, the study observed a positive impact of technological skills on women empowerment. It indicates that technology skills help women to start their new venture. In addition, the study observed a negative impact of security issue on women empowerment. It indicates that the number of security issues (gender inequality, Violence against women, inequality in power and decision making etc.) are higher, lower would be the women empowerment.